Effect of heat stress on age at first calving in Mehsana buffaloes under field progeny testing programme - Purohit, Pravin B; Gupta, Jay Prakash; Chaudhari, Jagdish D; Bhatt, Tanvir M; Pawar, Mahesh M; Srivastava, Amit K; Patel, Mayank P; Patel, P A; Prajapati, M N (Indian Journal of Dairy Science, 2021)
he records of 7791 Mehsana buffaloes sired by 182 sires on age at first calving (AFC) spread over a period of 24 years (1989 to 2012), collected from Dudhsagar Research and Development Association (DURDA), Dudhsagar Dairy, Mehsana. Meteorological data of the region (where field progeny testing was undergoing), were collected from the center of Indian Meteorological Department (IMD), Pune to know the association of AFC with heat stress indicators. The least squares mean and heritability of AFC were estimated. Various heat stress models were screened for optimization (Based on value of R2, adjusted R2, AIC and BIC) and effect of heat stress was quantified. Depending on the estimate of AFC and THI, months of the year were classified in to various heat stress zones. Sires were evaluated (both by BLUP-SM and BLUP-AM) for AFC in different HSZ, in order to identify optimum sire for each of the zone. The least squares mean estimate for AFC was 1419.61±2.18 days. The heritability estimates were obtained as 0.14±0.02 (LSML), 0.775±0.003 (BLUP-SM) and 0.13±0.023 (BLUP-AM). THI 6 model (Yousef, 1985) was found to be the best suited model and it was observed that AFC was declined by 1.26 day with per unit rise in THI. Year was classified in to NHSZ (non heat stress zone – November to March), HSZ (heat stress zone- April to October) and CHSZ (critical heat stress zone- June to August). The average breeding values of Mehsana buffalo bulls evaluated for AFC by BLUP-SM and BLUP-AM in NHSZ, HSZ and in CHSZ were estimated to be 1389.36, 1380.37 and 1375.04 days and 1389.33, 1382.85 and 1375.53 days, respectively. It was indicated that the bulls having superior performance in NHSZ were not as better performer in HSZ and CHSZ. This warrants that evaluation of bulls may be done separately in each heat stress zone and suitable bull for breeding under each HSZ may be identified.